A CFRP sheet reinforced concrete beam, reinforcement method and application
By pasting CFRP cloth with high-temperature magnesium phosphate inorganic adhesive pasting CFRP cloth reinforced concrete beams, the problem of insufficient fire safety of CFRP cloth reinforced structure in high-temperature environments is solved, and efficient reinforcement and fire resistance improvement of the structure are achieved.
Patent Information
- Application Number
- CN202410886986.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-03
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-07-03
AI Technical Summary
The fire safety of the CFRP cloth reinforced concrete structure is insufficient, resulting in failure of reinforcement under high temperature environments, resulting in structural damage or collapse.
The concrete beam is reinforced by CFRP cloth with high temperature resistant magnesium phosphate inorganic adhesive, which improves the thermal stability and corrosion resistance of the bonding layer.
It effectively reduces the fire safety risk of reinforced concrete beams, extends the service life of the structure, reduces maintenance costs, and improves the reinforced structure bearing capacity and fire resistance.
Smart Images

Figure CN118835828B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete structure reinforcement, and in particular relates to a concrete beam reinforced with CFRP cloth, a reinforcement method and application. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] The cement production industry is an industry with high energy consumption and high emissions. Strengthening and renovating existing buildings to improve the safety performance and usability of buildings in order to extend their service life can reduce the demand for new construction materials, maximize resource utilization, and reduce environmental pollution. For concrete structures, commonly used reinforcement methods include: increasing the cross-section method, replacing concrete method, bonding steel method, post-implantation steel method, etc. However, the above methods have problems such as a large increase in the self-weight of the structure, a reduction in the usable space (building floor height), a long construction period, and a short reinforcement life.
[0004] Carbon fiber-reinforced polymer (CFRP) cloth reinforcement method provides a new solution for the reinforcement of concrete structures. This method uses adhesive to stick CFRP cloth to the surface of the reinforced component to form a new composite component that works together with the original component to achieve the purpose of reinforcement. Compared with traditional reinforcement methods, CFRP cloth reinforcement method has the following advantages: (1) Lightweight and high strength. The tensile strength of CFRP cloth is 2 to 10 times that of steel, and the weight is only 20% of steel, which means that the effect of structural reinforcement can be achieved without significantly increasing the deadweight of the structure or reducing the usable space; (2) Good corrosion resistance. The durability of CFRP cloth in humid or chemically corrosive environments is better than that of traditional materials. This is particularly important for structural reinforcement in harsh environmental areas such as coastal areas, chemical workshops, and saline-alkali areas; (3) Strong adaptability. CFRP cloth can be cut into various shapes and sizes to meet the reinforcement needs of different structural types; (4) Simple construction. CFRP cloth reinforcement usually adopts the pasting method. The construction process is simple and fast, does not require large-scale demolition or reconstruction, and has little disturbance to the original structure and the surrounding environment.
[0005] However, the fire safety of CFRP cloth reinforced concrete structures has become a technical bottleneck that restricts its widespread application. This is because the adhesive used for CFRP cloth reinforcement is usually an epoxy organic adhesive, which has an extremely low glass transition temperature (only 65℃~82℃). When the temperature of the adhesive layer reaches the glass transition temperature during a fire, the epoxy organic adhesive softens rapidly, causing the bond strength between the CFRP cloth and the concrete matrix to drop sharply (only 20%~28% of the strength at room temperature), resulting in reinforcement failure, and then causing the reinforced structure to be severely damaged or collapsed. Although fire-retardant coatings, fire-retardant panels and other materials can be used to implement fire protection for CFRP cloth reinforced concrete structures to prevent adhesives and CFRP cloth from being directly exposed to high temperature environments and causing reinforcement failure, this will significantly increase the cost of structural reinforcement. At the same time, when the fire-retardant coating or fire-retardant panel is thick, measures such as hanging wire mesh or mechanical anchoring are required to prevent the fire protection layer from falling off. These construction processes are relatively complex and have a long construction period, and are not suitable for large-scale and wide-area concrete reinforcement projects.
[0006] Based on this, it is urgent to propose a method for strengthening concrete beams with CFRP sheets to solve the above technical problems. Summary of the invention
[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a concrete beam reinforced with CFRP cloth, a reinforcement method and application, and to use a high temperature resistant magnesium phosphate inorganic adhesive to adhere CFRP cloth to reinforce the concrete beam. It can reduce the fire safety risk of the reinforced concrete beam, and reduce the frequency of periodic inspection and maintenance, thereby reducing maintenance costs.
[0008] In order to achieve the above object, the technical solution of the present invention is:
[0009] In a first aspect, a method for reinforcing a concrete beam with CFRP cloth comprises the following steps:
[0010] S1. Clean the surface of the concrete beam and seal the surface cracks;
[0011] S2, setting the bottom surface of the full span of the concrete beam as a strip-shaped CFRP cloth reinforcement area, and setting the bottom surface and side surface of the concrete beam support position and the 1 / 4 to 1 / 3 span position extending from the support to the center of the concrete beam as a U-shaped CFRP cloth reinforcement area;
[0012] S3, wetting the strip-shaped CFRP cloth reinforcement area set in S2, and after wetting the U-shaped CFRP cloth reinforcement area set in S2, coating the wetted area with a high temperature resistant magnesium phosphate inorganic slurry;
[0013] S4, wetting the cut CFRP cloth and pasting it on the high temperature resistant magnesium phosphate inorganic glue in the wetting area in S3;
[0014] S5. After the pasting in S4 is completed, the surface of the CFRP cloth is coated with a high temperature resistant magnesium phosphate inorganic slurry.
[0015] Optionally, the method for reinforcing a concrete beam with CFRP cloth further comprises the steps of:
[0016] S6. Maintain the reinforced concrete beams.
[0017] Optionally, in S1, the loose and weak layer on the surface of the concrete beam is removed, and the loose fragments, floating dust and other coarse particle impurities in the cracks on the surface of the concrete beam are removed.
[0018] Optionally, in S1, for fine independent cracks with a width less than 0.2 mm, the cracks are sealed by applying epoxy resin structural adhesive on the surface; for penetrating cracks, the cracks are sealed by injecting or pressure-injecting epoxy resin structural adhesive.
[0019] Optionally, in S2, the surface of the provided reinforcement area is roughened, and the edges of the U-shaped CFRP cloth reinforcement area are chamfered.
[0020] Optionally, the chamfer radius is not less than 20 mm.
[0021] Optionally, in S2, the U-shaped CFRP cloth reinforcement areas on both sides of the concrete beam are symmetrically distributed.
[0022] Optionally, in S3, the reinforcement area is cleaned of loose dust and other coarse impurities before wetting.
[0023] Optionally, in S3, the high temperature resistant magnesium phosphate inorganic slurry includes the following components in parts by mass: 100 parts of dead-burned magnesium oxide, 55-58 parts of potassium dihydrogen phosphate, 8-18 parts of glass powder, 1-3 parts of dipotassium ethylenediaminetetraacetate, 1-3 parts of borax, 0.8-1.0 parts of calcium chloride hexahydrate, and 26-28 parts of water.
[0024] Optionally, the preparation process includes:
[0025] (a) Pour the weighed potassium dihydrogen phosphate, glass powder, dipotassium ethylenediaminetetraacetate and borax into a blender and mix and stir for 1 min (the blender speed is 60-65 r / min);
[0026] (b) dissolving the weighed calcium chloride hexahydrate with 3 / 4 of the total amount of water, then pouring the calcium chloride solution into the mixture of step (a), and stirring evenly for 2 minutes (stirrer speed 60-65r / min);
[0027] (c) adding the weighed dead-burned magnesium oxide into the mixture of step (b), and stirring evenly for 2 minutes (stirrer speed 60-65r / min);
[0028] (d) Add the remaining 1 / 4 of the total amount of water to the mixture of step (c), and stir rapidly for 5 minutes (stirrer speed 120-130 r / min) to obtain the high temperature resistant magnesium phosphate inorganic slurry required for pasting the CFRP cloth.
[0029] Optionally, in S3, after wetting with water, a high temperature resistant magnesium phosphate inorganic slurry with a thickness of 5 to 7 mm is applied.
[0030] Optionally, in S4, CFRP cloth is pasted in the strip-shaped CFRP cloth reinforcement area, the length of the CFRP cloth is the same as the span size of the concrete beam, the width of the CFRP cloth is determined based on the design value of the bending bearing capacity, and the fiber direction of the CFRP cloth is consistent with the span direction of the concrete beam.
[0031] Optionally, in S4, in the U-shaped CFRP cloth reinforcement area, the CFRP cloth is pasted in a direction perpendicular to the span of the concrete beam, the length of the CFRP cloth is the same as the sum of the bottom width and twice the side height of the concrete beam, the width of the CFRP cloth is determined based on the design value of the bending bearing capacity, and the fiber direction of the CFRP cloth is consistent with the length direction of the CFRP cloth.
[0032] Optionally, the width of the CFRP cloth used in the strip-shaped CFRP cloth reinforcement area and the U-shaped CFRP cloth reinforcement area is the same, and the method for determining the width of the CFRP cloth includes the steps of:
[0033] Step 1: Calculate the height x of the concrete compression zone:
[0034]
[0035] Step 2: Calculate the CFRP strength utilization coefficient ψ based on the obtained concrete compression zone height f :
[0036]
[0037] Step 3: Calculate the effective cross-sectional area A of the CFRP cloth based on the obtained concrete compression zone height and the obtained CFRP strength utilization coefficient fe :
[0038] α1f c0 bx=f y0 A s0 +ψ f f f A fe -f' y0 A' s0 (3)
[0039] Step 4: Calculate the width b0 of the pasted CFRP cloth according to the obtained effective cross-sectional area and CFRP thickness reduction coefficient:
[0040] b0=A fe / (k m ·t f ·ψ a ) (4)
[0041] In formula (1) to formula (4), M is the design value of the bending bearing capacity of the reinforced concrete beam; x is the height of the concrete compression zone; b and h are the cross-sectional width and cross-sectional height of the concrete beam, respectively; c is the thickness of the high-temperature resistant magnesium phosphate inorganic glue; α1 is the stress coefficient of the concrete compression zone; f y0 、f' y0 are the design values of tensile strength and compressive strength of the tensile reinforcement respectively; A s0 , A' s0 are the cross-sectional areas of the tensile reinforcement and the compressive reinforcement, respectively; a' is the distance from the combined force point of the compressive reinforcement to the near side of the concrete beam section; h0 is the effective height of the concrete beam section before reinforcement; f f A is the design value of CFRP cloth tensile strength; fe is the effective cross-sectional area of CFRP cloth; ψ f is the CFRP strength utilization coefficient, when ψ f >1.0, take ψ f =1.0;ε cu is the ultimate compressive strain of concrete, taken as 0.0033; ε f k is the design value of CFRP braid strain; m is the CFRP thickness reduction factor, which is taken as 0.90; t f is the thickness of a single layer of CFRP cloth; ψ a is the influence coefficient of inorganic glue, which is taken as 0.85.
[0042] Optionally, in S4, the CFRP cloth in the U-shaped CFRP cloth reinforcement area is adhered to the outer side of the CFRP cloth in the strip-shaped CFRP cloth reinforcement area.
[0043] Optionally, in S5, the coating thickness of the high temperature resistant magnesium phosphate inorganic slurry is 5 to 7 mm.
[0044] Optionally, in S6, the curing includes: natural curing at room temperature for 7 days.
[0045] In a second aspect, the CFRP sheet reinforced concrete beam is reinforced by the above-mentioned CFRP sheet reinforced concrete beam method.
[0046] On the third aspect, the reinforcement method of the above-mentioned CFRP cloth reinforced concrete beam and / or the application of the concrete beam reinforced with CFRP cloth include: application in concrete beam reinforcement projects in corrosive environments such as oceans, salt lakes, and chemical workshops; or, application in concrete beam reinforcement projects that need to improve the fire resistance level after reinforcement with CFRP cloth; or, application in concrete beam reinforcement projects in high temperature working environments such as steel mills and refineries.
[0047] The beneficial effects of the present invention are:
[0048] 1. The method of reinforcing concrete beams by pasting CFRP cloth based on high temperature resistant magnesium phosphate inorganic glue of the present invention gives full play to the advantages of CFRP cloth such as light weight, high strength, good corrosion resistance, strong adaptability, and simple construction, does not require large-scale demolition or reconstruction, and has little disturbance to the original structure and the surrounding environment, solving the problems of large increase in structural deadweight, reduced use space (building floor height), long construction period, and short reinforcement life in traditional concrete reinforcement methods. In addition, the high temperature resistant magnesium phosphate inorganic glue used has good thermal stability, does not shrink, crack, or deform after experiencing high temperatures above 1000°C, and also has strong resistance to corrosive environments such as acids, alkalis, and salts, ensuring its stability as an adhesive in extreme environments such as high temperature and corrosion, solving the problem of poor durability of traditional epoxy organic glues and the need for frequent periodic inspections, effectively reducing the maintenance cost of the reinforced structure, and expanding the scope of application of CFRP reinforcement technology.
[0049] 2. The high temperature resistant magnesium phosphate inorganic adhesive used in the present invention has high bonding strength and can form a reliable bonding layer between the CFRP cloth and the concrete beam, so that the two are firmly combined and bear force together, thereby significantly improving the bearing capacity of the reinforced concrete beam compared to the unreinforced concrete beam, providing a solid guarantee for the safety and reliability of the reinforced concrete beam; and the concrete beam reinforced with CFRP cloth adhered to the high temperature resistant magnesium phosphate inorganic adhesive has a bending bearing capacity at room temperature similar to that of the concrete beam reinforced with CFRP cloth adhered to the epoxy organic adhesive, that is, the present invention proposes an economical and efficient CFRP reinforcement method using inorganic adhesive instead of traditional epoxy organic adhesive as adhesive.
[0050] 3. The high temperature resistant magnesium phosphate inorganic glue used in the present invention has a slow degradation of bonding performance at high temperature. After 600°C, its bonding strength is still about 15% of the strength at room temperature, while the epoxy organic glue has completely lost its bonding strength at 200°C, ensuring the bonding reliability between the CFRP cloth and the concrete beam at high temperature; at the same time, the base glue-CFRP cloth-surface glue sandwich design of the present invention provides an anaerobic environment for the CFRP cloth to a certain extent, which can give full play to the excellent mechanical properties of the CFRP cloth under anaerobic conditions. The above two points make the fire resistance of the concrete beam reinforced by the present invention significantly improved compared with the concrete beam reinforced by epoxy organic glue, solve the problem that the epoxy organic glue is not resistant to high temperature, and improve the fire safety of the reinforced concrete beam. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0052] Figure 1 The flowchart is a method for reinforcing concrete beams with CFRP sheets in a specific implementation manner.
[0053] Figure 2 This is the reinforcement diagram of the concrete beam in Example 1 (unit: mm).
[0054] Figure 3 Schematic diagram of CFRP cloth layout on the side of the concrete beam in Example 1 (unit: mm).
[0055] Figure 4 Schematic diagram of CFRP cloth layout on the bottom surface of the concrete beam in Example 1 (unit: mm).
[0056] Figure 5 This is a physical picture of the first group of reinforced beams in Example 1.
[0057] Figure 6 Schematic diagram of the loading device for checking concrete beams at room temperature in Example 1.
[0058] Figure 7 This is a physical picture of the normal temperature verification concrete beam loading device in Example 1.
[0059] Figure 8 This is the load-mid-span deflection curve of the concrete beam checked at room temperature in Example 1.
[0060] Fig. 9 This is the failure morphology diagram of the original beam checked at room temperature in Example 1.
[0061] Fig.10 This is the failure morphology diagram of the second group of reinforced beams checked at room temperature in Example 1.
[0062] Fig.11 This is the failure morphology diagram of the first group of reinforced beams checked at room temperature in Example 1.
[0063] Fig.12 This is a comparison chart of the bending bearing capacity of concrete beams verified at room temperature in Example 1.
[0064] Fig.13 Schematic diagram of the high temperature verification concrete beam loading device in Example 1 (unit: mm).
[0065] Fig.14 This is a physical picture of the high temperature verification concrete beam loading device in Example 1.
[0066] Fig.15 This is a comparison chart of the mid-span deflection-fire time curve of the high-temperature verification concrete beam in Example 1.
[0067] Fig.16 This is the failure morphology diagram of the first group of reinforced beams in high temperature verification in Example 1.
[0068] Fig.17 This is a comparison chart of the fire resistance limits of concrete beams verified at high temperature in Example 1.
[0069] Fig.18 This is the apparent characteristic diagram of the high temperature resistant magnesium phosphate inorganic glue test block in Example 2 after being subjected to different temperatures.
[0070] Fig.19 Schematic diagram of the double shear test specimen of the interface after high temperature in Example 3 (unit: mm).
[0071] Fig. 20 Schematic diagram of the double shear test device for the interface after high temperature in Example 3 (unit: mm).
[0072] Fig.21 This is a comparison chart of the interface double shear test results after high temperature in Example 3.
[0073] Among them, 1. Concrete beam; 2. Strip CFRP cloth; 3. U-shaped CFRP cloth; 4. High temperature resistant magnesium phosphate inorganic glue; 5. Sliding hinge support; 6. Fixed hinge support; 7. Reaction frame; 8. Hydraulic jack; 9. Pressure sensor; 10. Distribution beam; 11. Displacement meter; 12. Anti-fall support; 13. Displacement meter support device; 14. Refractory cotton; 15. Concrete specimen; 16. High temperature test furnace; 17. Temperature controller; 18. Semicircular pad; 19. Oil pump; 20. Square pad; 21. Digital display. DETAILED DESCRIPTION
[0074] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0075] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0076] A method for reinforcing concrete beams with CFRP sheets, such as Figure 1 As shown, the following steps are included:
[0077] S1. Clean the surface of the concrete beam and seal the surface cracks;
[0078] S2, setting the bottom surface of the full span of the concrete beam as a strip-shaped CFRP cloth reinforcement area, and setting the bottom surface and side surface of the concrete beam support position and the 1 / 4 to 1 / 3 span position extending from the support to the center of the concrete beam as a U-shaped CFRP cloth reinforcement area;
[0079] S3, wetting the strip-shaped CFRP cloth reinforcement area set in S2, and after wetting the U-shaped CFRP cloth reinforcement area set in S2, coating the wetted area with a high temperature resistant magnesium phosphate inorganic slurry;
[0080] S4, wetting the cut CFRP cloth and pasting it on the high temperature resistant magnesium phosphate inorganic glue in the wetting area in S3;
[0081] S5. After the pasting in S4 is completed, the surface of the CFRP cloth is coated with a high temperature resistant magnesium phosphate inorganic slurry.
[0082] Optionally, the method for reinforcing a concrete beam with CFRP cloth further comprises the steps of:
[0083] S6. Maintain the reinforced concrete beams.
[0084] Optionally, in S1, an angle grinder is used to remove loose and weak layers on the surface of the concrete beam, and a blower is used to remove loose fragments, floating dust and other coarse particle impurities in cracks on the surface of the concrete beam.
[0085] Optionally, in S1, for fine independent cracks with a width less than 0.2 mm, the cracks are sealed by applying epoxy resin structural adhesive on the surface; for penetrating cracks, the cracks are sealed by injecting or pressure-injecting epoxy resin structural adhesive.
[0086] Optionally, in S2, the surface of the provided reinforcement area is roughened, and the edges of the U-shaped CFRP cloth reinforcement area are chamfered using an angle grinder, with the chamfer radius being not less than 20 mm.
[0087] Optionally, in S2, the U-shaped CFRP cloth reinforcement areas on both sides of the concrete beam are symmetrically distributed.
[0088] Optionally, in S3, use a broom to remove loose dust and other coarse particles from the reinforcement area before wetting.
[0089] Optionally, in S3, the high temperature resistant magnesium phosphate inorganic slurry includes the following components in parts by mass: 100 parts of dead-burned magnesium oxide, 55-58 parts of potassium dihydrogen phosphate, 8-18 parts of glass powder, 1-3 parts of dipotassium ethylenediaminetetraacetate, 1-3 parts of borax, 0.8-1.0 parts of calcium chloride hexahydrate, and 26-28 parts of water.
[0090] Optionally, the preparation process includes:
[0091] (a) Pour the weighed potassium dihydrogen phosphate, glass powder, dipotassium ethylenediaminetetraacetate and borax into a blender and mix and stir for 1 min (the blender speed is 60-65 r / min);
[0092] (b) dissolving the weighed calcium chloride hexahydrate with 3 / 4 of the total amount of water, then pouring the calcium chloride solution into the mixture of step (a), and stirring evenly for 2 minutes (stirrer speed 60-65r / min);
[0093] (c) adding the weighed dead-burned magnesium oxide into the mixture of step (b), and stirring evenly for 2 minutes (stirrer speed 60-65r / min);
[0094] (d) Add the remaining 1 / 4 of the total amount of water to the mixture of step (c), and stir rapidly for 5 minutes (stirrer speed 120-130 r / min) to obtain the high temperature resistant magnesium phosphate inorganic slurry required for pasting the CFRP cloth.
[0095] Optionally, in S3, a spray pot is used to wet the surface with water, and then a high temperature resistant magnesium phosphate inorganic slurry is applied with a thickness of 5 to 7 mm.
[0096] Optionally, in S4, CFRP cloth is pasted in the strip-shaped CFRP cloth reinforcement area, the length of the CFRP cloth is the same as the span size of the concrete beam, the width of the CFRP cloth is determined based on the design value of the bending bearing capacity, and the fiber direction of the CFRP cloth is consistent with the span direction of the concrete beam.
[0097] Optionally, in S4, in the U-shaped CFRP cloth reinforcement area, the CFRP cloth is pasted in a direction perpendicular to the span of the concrete beam, the length of the CFRP cloth is the same as the sum of the bottom width and twice the side height of the concrete beam, the width of the CFRP cloth is determined based on the design value of the bending bearing capacity, and the fiber direction of the CFRP cloth is consistent with the length direction of the CFRP cloth. Specifically, the size of the concrete beam is L0×b×h (span×section width×section height), then the size of the strip CFRP cloth reinforcement area at the bottom of the concrete beam is L0×b0 (length×width), so the length of the strip CFRP cloth is L0, and the width is b0; the two side surfaces at the concrete beam support position and the 1 / 3 span position extending from the support to the center of the concrete beam are the U-shaped CFRP cloth reinforcement area, which is a rectangle with a size of h×b0 (length×width), and the bottom surface at the concrete beam support position and the 1 / 3 span position extending from the support to the center of the concrete beam is also the U-shaped CFRP cloth reinforcement area, which is a rectangle with a size of b×b0 (length×width), so the length of the U-shaped CFRP cloth is b+2h, and the width is b0.
[0098] Optionally, the width of the CFRP cloth used in the strip-shaped CFRP cloth reinforcement area and the width of the CFRP cloth used in the U-shaped CFRP cloth reinforcement area are the same, both being b0. The method for determining the CFRP cloth width value b0 comprises the steps of:
[0099] Step 1: Calculate the height x of the concrete compression zone:
[0100]
[0101] Step 2: Calculate the CFRP strength utilization coefficient ψ based on the obtained concrete compression zone height f :
[0102]
[0103] Step 3: Calculate the effective cross-sectional area A of the CFRP cloth based on the obtained concrete compression zone height and the obtained CFRP strength utilization coefficient fe :
[0104] α1f c0 bx=f y0 A s0 +ψ f f f A fe -f' y0 A's0 (3)
[0105] Step 4: Calculate the CFRP cloth pasting width b0 based on the obtained effective cross-sectional area and CFRP thickness reduction coefficient:
[0106] b0=A fe / (k m ·t f ·ψ a ) (4)
[0107] In formula (1) to formula (4), M is the design value of the bending bearing capacity of the reinforced concrete beam; x is the height of the concrete compression zone; b and h are the cross-sectional width and cross-sectional height of the concrete beam, respectively; c is the thickness of the high-temperature resistant magnesium phosphate inorganic glue; α1 is the stress coefficient of the concrete compression zone; f y0 、f' y0 are the design values of tensile strength and compressive strength of the tensile reinforcement respectively; A s0 , A' s0 are the cross-sectional areas of the tensile reinforcement and the compressive reinforcement, respectively; a' is the distance from the combined force point of the compressive reinforcement to the near side of the concrete beam section; h0 is the effective height of the concrete beam section before reinforcement; f f A is the design value of CFRP cloth tensile strength; fe is the effective cross-sectional area of CFRP cloth; ψ f is the CFRP strength utilization coefficient, when ψ f >1.0, take ψ f =1.0;ε cu is the ultimate compressive strain of concrete, taken as 0.0033; ε f k is the design value of CFRP braid strain; m is the CFRP thickness reduction factor, which is taken as 0.90; t f is the thickness of a single layer of CFRP cloth; ψ a is the influence coefficient of inorganic glue, which is taken as 0.85.
[0108] Optionally, in S4, the CFRP cloth in the U-shaped CFRP cloth reinforcement area is adhered to the outer side of the CFRP cloth in the strip-shaped CFRP cloth reinforcement area.
[0109] Optionally, in S4, the strip-shaped CFRP cloth is first moistened and then pasted on the high-temperature resistant magnesium phosphate inorganic glue at the bottom of the concrete beam, so that the fiber direction of the CFRP cloth is consistent with the span direction of the concrete beam; then the U-shaped CFRP cloth is moistened and passed around the bottom of the concrete beam, and pasted on the high-temperature resistant magnesium phosphate inorganic glue on the two side surfaces and one bottom surface of the concrete beam; finally, a roller is used to repeatedly scrape and brush along the fiber direction of the CFRP cloth to allow the high-temperature resistant magnesium phosphate inorganic glue to fully infiltrate the CFRP cloth and expel the bubbles inside.
[0110] Optionally, in S5, the coating thickness of the high temperature resistant magnesium phosphate inorganic adhesive is 5 to 7 mm. After coating, a roller is used to repeatedly scrape and brush along the fiber direction of the CFRP cloth to allow the high temperature resistant magnesium phosphate inorganic adhesive to fully infiltrate the CFRP cloth and expel internal bubbles.
[0111] Optionally, in S6, the curing includes: natural curing at room temperature for 7 days.
[0112] A CFRP cloth reinforced concrete beam obtained by using the above-mentioned CFRP cloth reinforced concrete beam reinforcement method.
[0113] A reinforcement method for the above-mentioned CFRP cloth reinforced concrete beam and / or an application of the above-mentioned CFRP cloth reinforced concrete beam, including: (1) application in concrete beam reinforcement projects in corrosive environments such as oceans, salt lakes, and chemical workshops; (2) application in concrete beam reinforcement projects that need to improve the fire resistance level after reinforcement with CFRP cloth; (3) application in concrete beam reinforcement projects in high-temperature working environments such as steel mills and refineries.
[0114] Example 1
[0115] Five concrete beams 1 were prepared using the same raw materials and methods, such as Figure 2 As shown, the beam span L0 is 3300mm, the calculated span is 3000mm, the cross-sectional dimensions b×h are 150mm×300mm (cross-sectional width×cross-sectional height), the concrete strength grade is C30, the steel strength grade is HRB400, and the reinforcement of concrete beam 1 is as follows: Figure 2 Two specifications are shown: 8mm diameter and 12mm diameter.
[0116] According to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T 50081-2019), the measured compressive strength of concrete cube is 30.6MPa; according to the "Tensile Test of Metallic Materials Part 1: Room Temperature Test Method" (GB / T 228.1-2021), the measured mechanical properties of steel bars are as follows: the yield strength of steel bars with a diameter of 8mm is 446MPa, and the ultimate tensile strength is 603MPa; the yield strength of steel bars with a diameter of 12mm is 435MPa, and the ultimate tensile strength is 588MPa.
[0117] According to the method of the present invention, two concrete beams are reinforced as the first group of reinforced beams, and the steps include: S1, cleaning the surface of the concrete beams and sealing the surface cracks;
[0118] S2. The bottom surface of the full span of the concrete beam is set as a strip-shaped CFRP cloth reinforcement area, and the bottom and side surfaces of the concrete beam support (including the 300 mm range at both ends) and the 1 / 3 span position extending from the support to the center of the concrete beam (including the 1 / 3 position and the 2 / 3 position of the span respectively) are set as U-shaped CFRP cloth reinforcement areas;
[0119] S3, wetting the strip-shaped CFRP cloth reinforcement area set in S2, and after wetting the U-shaped CFRP cloth reinforcement area set in S2, coating the wetted area with a 5 mm thick high temperature resistant magnesium phosphate inorganic slurry;
[0120] Specifically, the magnesium phosphate inorganic slurry used in this embodiment includes the following components in parts by mass: 100 parts of dead-burned magnesium oxide, 56.7 parts of potassium dihydrogen phosphate, 17.4 parts of glass powder, 2 parts of dipotassium ethylenediaminetetraacetate, 2 parts of borax, 0.9 parts of calcium chloride hexahydrate, and 27.8 parts of water;
[0121] The preparation process includes:
[0122] (a) Pour the weighed potassium dihydrogen phosphate, glass powder, dipotassium ethylenediaminetetraacetate and borax into a blender and mix and stir for 1 min (the blender speed is 60 r / min);
[0123] (b) dissolving the weighed calcium chloride hexahydrate with 3 / 4 of the total amount of water, then pouring the calcium chloride solution into the mixture of step (a), and stirring evenly for 2 minutes (stirrer speed 60r / min);
[0124] (c) adding the weighed dead-burned magnesium oxide into the mixture of step (b) and stirring evenly for 2 minutes (stirrer speed 60r / min);
[0125] (d) adding the remaining 1 / 4 of the total amount of water to the mixture of step (c), and rapidly stirring for 5 minutes (stirrer speed 125 r / min), to obtain the high temperature resistant magnesium phosphate inorganic slurry required for pasting the CFRP cloth;
[0126] According to the "Test Method for Cement Mortar Strength" (GB / T 17671-2021), the measured mechanical properties of high-temperature resistant magnesium phosphate inorganic glue are as follows: tensile strength is 5.5MPa, flexural strength is 9.5MPa, and compressive strength is 43.2MPa.
[0127] S4, such as Figure 3-4 As shown, the cut CFRP cloth is wetted and then pasted on the high temperature resistant magnesium phosphate inorganic glue in the wetted area of S3;
[0128] Specifically, the CFRP cloth used is RLS-I-300 CFRP cloth produced by Shanghai Zhinuo Decoration Materials Co., Ltd., with a thickness of 0.167 mm and a density of 300 g / m 2 , the tensile strength is 3668MPa, the elastic modulus is 240GPa, and the elongation is 1.74%.
[0129] like Figure 4 As shown, the strip-shaped CFRP cloth 2 has a length L0 of 3300 mm and a width b0 of 100 mm and is pasted on the bottom surface of the concrete beam 1; Figure 3 As shown, the length 2h+b of the U-shaped CFRP cloth 3 is 2×300mm+150mm=750mm, and the width b0 is 100mm. It is pasted on the bottom surface and front and rear side surfaces of the support of the concrete beam 1 (including the 300mm range at both ends respectively) and the 1 / 3 span position extending from the support to the center of the concrete beam (including the 1 / 3 position and the 2 / 3 position of the span respectively); the U-shaped CFRP cloth 3 is pasted on the outside of the strip-shaped CFRP cloth 2.
[0130] The calculation method of b0 is:
[0131] Step 1: Calculate the height x of the concrete compression zone:
[0132]
[0133] Step 2: Calculate the CFRP strength utilization coefficient ψ based on the obtained concrete compression zone height x f :
[0134]
[0135] CFRP strength utilization coefficient ψ f Take 1.0;
[0136] Step 3: Based on the obtained concrete compression zone height x and the obtained CFRP strength utilization coefficient ψ f Calculate the effective cross-sectional area A of CFRP cloth fe :
[0137] α1f c0 bx=f y0 A s0 +ψ f f f A fe -f' y0 A' s0
[0138] 1.0×30×10 6 Pa 0.15m 0.01m = 360 × 10 6 Pa 226×10 -6m+1.0×3668
[0139] ×10 6 Pa.A fe -360×10 6 Pa 226×10 -6 m
[0140] A fe =1.23×10 -5 m 2 (3)
[0141] Step 4: According to the effective cross-sectional area A fe and CFRP thickness reduction factor k m Calculate the CFRP cloth pasting width b0:
[0142]
[0143] Finally, b0 is taken as 0.1m, that is, b0=100mm.
[0144] S5, such as Figure 5 As shown, after the pasting is completed in S4, the surface of the CFRP cloth is coated with a 5 mm thick slurry of high temperature resistant magnesium phosphate inorganic glue 4;
[0145] S6. Natural curing at room temperature for 7 days to complete the reinforcement process.
[0146] According to the provisions of the "Technical Standard for Engineering Application of Fiber Reinforced Composite Materials" (GB 50608-2020), another concrete beam was reinforced with CFRP cloth bonded with epoxy organic adhesive as the second group of reinforced beams. The specifications, dimensions and layout of the CFRP cloth used were the same as those of the first group of reinforced beams; the mechanical properties of the epoxy organic adhesive used in the second group of reinforced beams are as follows: tensile strength is 48.8MPa, flexural strength is 93.8MPa, and compressive strength is 97.2MPa.
[0147] Take another two concrete beams without reinforcement and use them as original beams.
[0148] Normal temperature calibration
[0149] According to the provisions of the "Standard for Test Methods of Concrete Structures" (GB / T 50152-2012), the samples of the original beams, the first group of reinforced beams and the second group of reinforced beams were tested, that is, two symmetrical concentrated loads were applied to each concrete beam, and then graded loading was performed using a load control method until the concrete beam was destroyed. The schematic diagram of the concrete beam loading device is shown in Figure 6As shown: the bottom ends of the concrete beam 1 are simply supported by sliding hinge supports 5 and fixed hinge supports 6, the upper surface of the 1 / 3 span position and the 2 / 3 span position of the concrete beam 1 is connected to the distribution beam 10 through the sliding hinge supports 5 and the fixed hinge supports 6, the hydraulic jack 8 fixed on the reaction frame 7 presses the distribution beam 10 downward to load the concrete beam 1, and the load is P; a pressure sensor 9 is arranged between the hydraulic jack 8 and the distribution beam 10 to measure the applied load value, and displacement meters 11 are respectively arranged on the upper surface of the support positions at both ends of the concrete beam 1, and displacement meters 11 are respectively arranged on the lower surface of the 1 / 3, 1 / 2 and 2 / 3 positions of the span of the concrete beam 1; the actual picture of the concrete beam loading device is as shown in Figure 7 shown.
[0150] The test results show that the load-mid-span deflection curve of the concrete beam in the static load test at room temperature is as follows: Figure 8 As shown in the figure, at the initial loading stage, the concrete beams did not crack and were in the elastic stage; when loaded to 0.2P u (P u When the load is the ultimate load, each concrete beam enters the elastic-plastic stage, fine cracks appear, and the stiffness begins to decrease. The bending stiffness of each concrete beam in the elastic and elastic-plastic stages is roughly the same; when loaded to 0.75-0.85Pu, each concrete beam enters the plastic stage, and the load-mid-span deflection curve shows an obvious inflection point, the bending stiffness decreases significantly, and the mid-span deflection develops faster: in this stage, the original beam's stiffness decays the fastest and its ability to resist deformation is the worst, while the reinforced beams (the first group of reinforced beams and the second group of reinforced beams) still have good stiffness performance. The CFRP cloth and the concrete beams are reliably bonded, and the two are subjected to force in coordination, which plays a role in limiting the deformation and crack development of the concrete beams, thereby significantly improving the bending bearing capacity of the reinforced beams compared to the original beams, providing a solid guarantee for the safety and reliability of the reinforced concrete beams.
[0151] In the static load test at room temperature, the failure mode of the original beam is as follows: Fig. 9 As shown in the figure, it is a typical reinforcement failure mode; the failure mode of the second group of reinforced beams is as follows Fig.10 As shown in the figure, the concrete in the compression zone was crushed, the CFRP sheet broke and peeled off from the concrete beam on a large scale; the failure mode of the first group of reinforced beams is shown in Fig.11 As shown in the figure, the concrete in the compression zone is crushed, and the CFRP sheet and the adhesive layer at the main crack position slip relative to each other. Comparing the failure forms of each concrete beam, it can be seen that the crack spacing of the reinforced beams (the first group of reinforced beams and the second group of reinforced beams) is larger than that of the original beams; the cracks of the second group of reinforced beams are densely distributed and the spacing is small; due to the large stiffness of the adhesive layer, it can effectively inhibit the development of cracks, and the cracks of the first group of reinforced beams are sparsely distributed and the spacing is large.
[0152] Comparison of bending bearing capacity of concrete beams in static load test at room temperature Fig.12As shown, the bending bearing capacity of the original beam is 21kN·m, the bending bearing capacity of the second group of reinforced beams is 29.5kN·m, and the bending bearing capacity of the first group of reinforced beams is 27.5kN·m. The results of the static load test at room temperature show that the bending bearing capacity of the reinforced beam is significantly improved compared with the original beam, and the bending bearing capacity of the concrete beam reinforced with CFRP cloth based on high temperature resistant magnesium phosphate inorganic glue at room temperature is similar to that of the concrete beam reinforced with CFRP cloth based on epoxy organic glue, that is, the present invention proposes an economical and efficient CFRP reinforcement method using inorganic glue instead of traditional epoxy organic glue as adhesive.
[0153] High temperature check
[0154] According to the provisions of the "Fire Resistance Test Method for Building Components" (GB / T 9978-2008), the samples in the first group of reinforced beams and original beams were tested. Since the glass transition temperature of the epoxy organic adhesive used in the second group of reinforced beams is only 65℃~82℃, after reaching the glass transition temperature, the bonding performance of the epoxy organic adhesive will rapidly deteriorate, resulting in reinforcement failure. Therefore, when a fire occurs, the fire resistance of the concrete beams reinforced with epoxy organic adhesive is basically the same as that of the unreinforced concrete beams. Therefore, the samples in the concrete beams reinforced with epoxy organic adhesive (i.e. the second group of reinforced beams) were not tested.
[0155] Schematic diagram of fire resistance test loading device Fig.13 As shown, a concrete beam 1 is placed in the furnace of a fire test furnace, and the two ends of the bottom of the concrete beam 1 are simply supported by a sliding hinge support 5 and a fixed hinge support 6 respectively. The upper surface of the concrete beam 1 at the 1 / 3 span position is connected to the distribution beam 10 through the sliding hinge support 5 and the fixed hinge support 6. The hydraulic jack 8 fixed on the reaction frame 7 presses the distribution beam 10 downward, and two symmetrical concentrated loads are applied to the concrete beam 1. The total load value is P. A pressure sensor 9 is arranged between the hydraulic jack 8 and the distribution beam 10 to measure the applied load value; displacement meters 11 are respectively arranged on the upper surface of the support positions at both ends of the concrete beam 1, and a displacement meter support device 13 is arranged on the upper surface of the mid-span position of the concrete beam 1 to support the displacement meter 11 for measuring the mid-span deflection of the concrete beam 1; an anti-fall support 12 is arranged below the concrete beam 1 to ensure safety. Concrete beam 1 is heated by constant load, with a load level of 0.4. The furnace of the fire test furnace is heated according to the ISO834 standard heating curve. The two sides and bottom of concrete beam 1 are exposed to fire. The load remains constant during the heating process. The mid-span deflection reaches 1 / 20 of the calculated span as the standard for concrete beam 1 to reach the fire resistance limit. After reaching the fire resistance limit, the concrete beam is unloaded, and the fire is stopped within 10 minutes, and it is cooled naturally to room temperature. Fig.14 As shown, in order to maintain the temperature, fire-resistant wool 14 is laid on the upper surface of the concrete beam 1 and the temperature-raising area.
[0156] Comparison of mid-span deflection-fire time curves of concrete beams Fig.15 As shown in the figure, under the same fire exposure time, the mid-span deflection of the first group of reinforced beams develops significantly slower than that of the original beams. At 70 minutes of fire exposure, the mid-span deflection-time curve of the original beams shows a steep rise and reaches the fire resistance limit, while the mid-span deflection-time curve of the first group of reinforced beams shows a steep rise 20 minutes later. The failure morphology of the first group of reinforced beams in the fire test is shown in the figure. Fig.16 As shown in the figure, the beam side and bottom had slight cracks, the strip-shaped CFRP cloth reinforcement area and the U-shaped CFRP cloth reinforcement area had good integrity, only part of the surface adhesive fell off, and the CFRP cloth did not undergo obvious oxidation. Fig.17 As shown, the fire resistance limit of the original beam is 70 minutes, and the fire resistance limit of the first group of reinforced beams is 90 minutes, which is 29% higher than the fire resistance limit of the original beam. The fire resistance test results show that the sandwich design of the base glue-CFRP cloth-surface glue of the present invention provides an anaerobic environment for the CFRP cloth to a certain extent, which can give full play to the excellent mechanical properties of the CFRP cloth under anaerobic conditions, and significantly improve the fire resistance of the concrete beam reinforced by the present invention, solve the problem of epoxy organic glue not being resistant to high temperature in CFRP reinforcement, and improve the fire safety of the reinforced concrete beam.
[0157] Example 2
[0158] The preparation method of the high-temperature resistant magnesium phosphate inorganic slurry in Example 1 was adopted to make 12 test blocks with a size of 40mm×40mm×160mm; the 12 test blocks were divided into 3 groups: the first group had 1 test block, which was placed at room temperature; the second group had 10 test blocks, which were heated to target temperatures of 100°C, 200°C, 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C and 1000°C at a heating rate of 10°C / min, and the heating was stopped after reaching the target temperature, allowing the test blocks to cool naturally to room temperature; the third group had 1 test block, which was heated for 2h according to the ISO834 standard heating curve, and then the heating was stopped, allowing the test block to cool naturally to room temperature.
[0159] The apparent characteristics of the high temperature resistant magnesium phosphate inorganic glue specimen after being subjected to different temperatures are as follows Fig.18As shown in the figure, when the overfire temperature is below 100℃, the surface of the test block is roughly khaki; when the overfire temperature rises to 300℃, the surface of the test block gradually turns to light yellow; when the overfire temperature rises to 400℃, the surface of the test block is gray; when the overfire temperature rises to 600℃, the surface of the test block is dark brown. When the overfire temperature is 700-1000℃, the surface color of the test block is basically the same, which is off-white; compared with the test blocks that have not experienced high temperature, the test blocks that have experienced high temperature have no obvious cracking, peeling, bursting and other phenomena, and the test blocks have no visual shrinkage deformation after experiencing 1000℃ high temperature. Under the ISO834 standard heating conditions, the test blocks still maintain integrity after heating for 2h, without obvious cracking, peeling, bursting and other phenomena, and the surface of the test block changes from khaki at room temperature to off-white.
[0160] The test results show that the high-temperature resistant magnesium phosphate inorganic adhesive used in the present invention has good thermal stability. After experiencing high temperatures above 1000°C, it does not shrink, crack or deform, ensuring its stability as an adhesive in extreme environments such as high temperatures. It solves the problems of traditional epoxy organic adhesives such as high fire safety risks, poor durability, and the need for frequent periodic inspections, effectively reduces the maintenance cost of reinforced structures, and expands the application scope of CFRP reinforcement technology.
[0161] Example 3
[0162] Ten specimens were made to conduct the interface double shear test after high temperature, and the ten specimens were divided into two groups: the first group of seven specimens used the high temperature resistant magnesium phosphate inorganic adhesive to bond the CFRP cloth; the first group of three specimens used the epoxy organic adhesive to bond the CFRP cloth. Fig.19As shown, the size of the concrete specimen 15 is 120mm×120mm×450mm, and the concrete strength grade is C30. The front and rear sides thereof are respectively pasted with strip-shaped CFRP cloth 2 with high temperature resistant magnesium phosphate inorganic glue 4. The bonding length of the strip-shaped CFRP cloth 2 is 100mm, the bonding width is 70mm, and the free lengths of the two ends of the strip-shaped CFRP cloth 2 on the concrete specimen 15 are 80mm and 50mm respectively. The pasting method is the same as that of Example 1. First, the surface of the concrete specimen 15 is cleaned, and then the area (100mm×70mm) on the surface of the concrete specimen 15 where the strip-shaped CFRP cloth 2 is to be pasted is roughened, and then the roughened area is moistened and coated with high temperature resistant magnesium phosphate inorganic glue 4. After pasting the strip-shaped CFRP cloth 2, the high temperature resistant magnesium phosphate inorganic glue 4 is coated, and then naturally cured at room temperature for 7 days. The interface double shear test specimen of CFRP cloth bonded with epoxy organic glue is the same as the interface double shear test specimen of CFRP cloth bonded with high temperature resistant magnesium phosphate inorganic glue except that the high temperature resistant magnesium phosphate inorganic glue 4 is replaced by epoxy organic glue. According to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T 50081-2019), the measured cubic compressive strength of concrete specimen 15 is 29.4MPa. The specifications of CFRP cloth, high temperature resistant magnesium phosphate inorganic glue and epoxy organic glue used are the same as those in Example 1, and the corresponding mechanical performance indicators are shown in Example 1.
[0163] Before the high temperature interface double shear test is carried out on the specimen, a high temperature test is first carried out on it. The heating device used for the high temperature test is as follows: Fig. 20 As shown in (a), a concrete specimen 15 with a strip-shaped CFRP cloth 2 is placed in a high-temperature test furnace 16. The temperature in the high-temperature test furnace 16 is controlled by a temperature controller 17. The top of the high-temperature test furnace 16 is covered with refractory wool 14 to prevent heat loss. For the seven interface double shear test specimens using high-temperature magnesium phosphate inorganic adhesive to bond CFRP cloth, the temperature is increased to 25°C, 100°C, 200°C, 300°C, 400°C, 500°C, 600°C and other target temperatures at a rate of 5°C / min. After the specimens are kept at the target temperature for 2.5 hours, they are taken out of the high-temperature test furnace 16 and naturally cooled to room temperature. For the three interface double shear test specimens using epoxy organic adhesive to bond CFRP cloth, the temperature is increased to 25°C, 100°C and 200°C at a rate of only 5°C / min. After the specimens are kept at the target temperature for 2.5 hours, they are taken out of the high-temperature test furnace 16 and naturally cooled to room temperature.
[0164] After the high temperature test, the specimen is subjected to a double shear test on the interface after high temperature. The test loading device is as follows: Fig. 20As shown in (b), the square pad 20, the pressure sensor 9, the hydraulic jack 8, and the semicircular pad 18 are placed on the upper part of the concrete specimen 15 in sequence; the strip-shaped CFRP cloth 2 of the concrete specimen 15 is passed around the semicircular pad 18, and the height of the hydraulic jack 8 and the pressure sensor 9 is adjusted to make the strip-shaped CFRP cloth 2 vertically straighten on both sides of the concrete specimen 15; the hydraulic jack 8 is driven by the oil pump 19 to apply an upward load P to the semicircular pad 18, so that the CFRP cloth on both sides of the concrete specimen 15 bears a tensile force of P / 2, and the tensile force makes the adhesive bear a shear force in the bonding area until the bonding fails and the loading ends. The square pad 20 is set between the pressure sensor 9 and the concrete specimen 15 to make the specimen bear uniform force during the entire loading process; the applied load value during the loading process is collected by the pressure sensor 9 and displayed by the digital display 21.
[0165] Comparison of interface double shear test results after high temperature Fig.21 As shown, the bar graph shows that the in-plane shear strength (indicating bonding strength) of the high temperature resistant magnesium phosphate inorganic glue at room temperature is slightly higher than that of the epoxy organic glue; the line graph shows the relative in-plane shear strength, which is the in-plane shear strength = in-plane shear strength at the test temperature / in-plane shear strength at room temperature, and can represent the degradation rate of the bonding strength during the temperature increase process; by comparing the relative in-plane shear strength of the magnesium phosphate inorganic glue and the epoxy organic glue, it can be seen that when the over-fire temperature is lower than 200°C, the degradation rate of the bonding strength of the epoxy organic glue is faster than that of the high temperature resistant magnesium phosphate inorganic glue. When the fire temperature reaches 200℃, the bonding strength of epoxy organic adhesive decreases by 86.6% compared with room temperature, while the bonding strength of high temperature resistant magnesium phosphate inorganic adhesive only decreases by 38.2% compared with room temperature; when the fire temperature reaches 600℃, the bonding strength of high temperature resistant magnesium phosphate inorganic adhesive is still about 15% of the strength at room temperature, while the bonding strength of epoxy organic adhesive is completely lost, which highlights the high temperature resistant advantage of magnesium phosphate inorganic adhesive as an adhesive for CFRP reinforced concrete structure and ensures the bonding reliability between CFRP cloth and concrete beam at high temperature.
[0166] It can be seen from the above performance test results that the present invention can maintain reliable bonding performance in a high temperature environment, and can therefore be applied to concrete beam reinforcement projects in high temperature working environments such as steel mills and oil refineries.
[0167] Since the CFRP cloth and the magnesium phosphate inorganic adhesive of the present invention can both play an anti-corrosion role, they can be applied to concrete beam reinforcement projects in corrosive environments such as oceans, salt lakes, and chemical workshops.
[0168] Since the technical solution of the present invention can play a role in fire resistance and only requires reinforcement on the surface of the concrete beam without destructive processing of the concrete beam, it can be applied to concrete beam reinforcement projects that have adopted conventional CFRP reinforcement methods but still need to improve the fire resistance level.
[0169] It should be noted that in the above embodiments, as long as the technical solutions are not contradictory, they can be arranged and combined, and those skilled in the art can exhaust all possibilities based on the mathematical knowledge of arrangement and combination. Therefore, the present invention will no longer describe the technical solutions after arrangement and combination one by one, but it should be understood that the technical solutions after arrangement and combination have been disclosed by the present invention.
[0170] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for reinforcing a concrete beam with CFRP cloth, characterized in that: The following steps are involved: S1. Clean the surface of the concrete beam and seal the surface cracks; S2, setting the bottom surface of the full span of the concrete beam as a strip-shaped CFRP cloth reinforcement area, and setting the bottom surface and side surface of the concrete beam support position and the 1 / 4 to 1 / 3 span position extending from the support to the center of the concrete beam as a U-shaped CFRP cloth reinforcement area; S3, wetting the strip-shaped CFRP cloth reinforcement area set in S2, and after wetting the U-shaped CFRP cloth reinforcement area set in S2, coating the wetted area with a high temperature resistant magnesium phosphate inorganic slurry; S4, wetting the cut CFRP cloth and pasting it on the high temperature resistant magnesium phosphate inorganic glue in the wetting area in S3; S5, coating the surface of the CFRP cloth after pasting in S4 with a high temperature resistant magnesium phosphate inorganic slurry; In S4, CFRP sheets are pasted in the strip-shaped CFRP sheet reinforcement area, the length of the CFRP sheet is the same as the span size of the concrete beam, the width of the CFRP sheet is determined based on the design value of the bending bearing capacity, and the fiber direction of the CFRP sheet is consistent with the span direction of the concrete beam; Optionally, in S4, in the U-shaped CFRP sheet reinforcement area, the CFRP sheet is pasted in a direction perpendicular to the span of the concrete beam, the length of the CFRP sheet is the same as the sum of the bottom width and twice the side height of the concrete beam, the width of the CFRP sheet is determined based on the design value of the bending bearing capacity, and the fiber direction of the CFRP sheet is consistent with the length direction of the CFRP sheet; Optionally, the width of the CFRP cloth used in the strip-shaped CFRP cloth reinforcement area and the U-shaped CFRP cloth reinforcement area is the same, and the method for determining the width of the CFRP cloth includes the steps of: Step 1: Calculate the height of the concrete compression zone; Step 2: Calculate the CFRP strength utilization factor based on the obtained concrete compression zone height; Step 3: Calculate the effective cross-sectional area of the CFRP cloth according to the obtained concrete compression zone height and the obtained CFRP strength utilization coefficient; Step 4: Calculate the CFRP cloth pasting width based on the obtained effective cross-sectional area and CFRP thickness reduction coefficient.
2. The method for reinforcing a concrete beam with CFRP cloth according to claim 1, characterized in that: The method comprises the steps of: S6, curing the reinforced concrete beam; Optional, curing includes: natural curing at room temperature for 7 days.
3. The method for reinforcing concrete beams with CFRP sheets according to claim 1, characterized in that: In S1, the loose and weak layer on the surface of the concrete beam is removed, and the loose debris, floating dust and other coarse particle impurities in the cracks on the surface of the concrete beam are removed; Optionally, in S1, for fine independent cracks with a width less than 0.2 mm, the cracks are sealed by applying epoxy resin structural adhesive on the surface; for penetrating cracks, the cracks are sealed by injecting or pressure-injecting epoxy resin structural adhesive.
4. The method for reinforcing a concrete beam with CFRP sheets as claimed in claim 1, characterized in that: In S2, the surface of the provided reinforcement area is roughened, and the edges of the U-shaped CFRP cloth reinforcement area are chamfered; Optionally, the chamfer radius is not less than 20 mm.
5. The method for reinforcing a concrete beam with CFRP sheets as claimed in claim 4, characterized in that: In S2, the U-shaped CFRP sheet reinforcement areas on both sides of the concrete beam are symmetrically distributed.
6. The method for reinforcing a concrete beam with CFRP sheets as claimed in claim 1, characterized in that: In S3, the high temperature resistant magnesium phosphate inorganic slurry includes the following components in parts by mass: 100 parts of dead burned magnesium oxide, 55-58 parts of potassium dihydrogen phosphate, 8-18 parts of glass powder, 1-3 parts of dipotassium ethylenediaminetetraacetate, 1-3 parts of borax, 0.8-1.0 parts of calcium chloride hexahydrate, and 26-28 parts of water; Optionally, in S3, after wetting with water, a high temperature resistant magnesium phosphate inorganic slurry with a thickness of 5 to 7 mm is applied.
7. The method for reinforcing a concrete beam with CFRP sheets as claimed in claim 1, characterized in that: In S5, the coating thickness of the high temperature resistant magnesium phosphate inorganic slurry is 5 to 7 mm.
8. A CFRP sheet reinforced concrete beam obtained by the method for reinforcing concrete beam with CFRP sheet as claimed in any one of claims 1 to 7.
9. A method for reinforcing a concrete beam reinforced with a CFRP sheet as claimed in any one of claims 1 to 7 and / or a use of a concrete beam reinforced with a CFRP sheet as claimed in claim 8, characterized in that: include: Applied to concrete beam reinforcement projects in corrosive environments such as oceans, salt lakes, and chemical plants; Alternatively, it can be used in concrete beam reinforcement projects where the fire resistance rating needs to be improved after being reinforced with CFRP sheets; Alternatively, it can be used in concrete beam reinforcement projects in high temperature working environments of steel mills and oil refineries.
Citation Information
Patent Citations
Method for strengthening concrete by applying magnesium phosphate cement and fiber cloth composite materials
CN103104100A
Method for carrying out shear-resistant reinforcement on beam with floor slab
CN110397300A